Determining mindful consumption among staff in government agency / Syahrul Hezrin Mahmud ... [et al.] - Mahmud, Syahrul Hezrin; Mat Yusof, Mohd Husnin; Mamat, Marini; Ibrahim @ Mat Nor, Mohd Ariff Nafizi (2018)
Sustainable consumption is one of the important discussions among consumers in Malaysia, due to the rising cost of living. This is because of the fluctuating of goods and services price, the introduction of new tax regime particularly Goods and Services Tax (GST) and the issue of uncontrollable debts caused by aggressive promotion by banking institution. This phenomenon has affected the spending pattern among Malaysians and it was highlighted in few literatures. Consequently, the importance of addressing the aspects of inculcating mindful consumption is crucially demanding and the comprehension of the topic should be fostered among consumers. The research on the subject matter is expected to bring a new paradigm toward practicing mindful consumption. Thus, the study aims to determine factors that affects mindful consumption among government staff and they were tested statistically. The study is conducted among the staff of Majlis Agama Islam Dan Adat Melayu Terengganu (MAIDAM) at its headquarters in Kuala Terengganu. MAIDAM is an agency that is responsible for the administration of Islamic religious affairs in Terengganu, Malaysia. There were 175 questionnaires administered to the respondents and all responses were analysed using the SPSS version 15. The results clearly indicate that all factors tested affected mindful consumption. The result also indicates that mindful consumption contributes benefits to the government servant and consumers in this country. It is undoubted that further research in this field among scholars and researchers is needed.